7(2n-4)-5=-40+7n

Simple and best practice solution for 7(2n-4)-5=-40+7n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2n-4)-5=-40+7n equation:


Simplifying
7(2n + -4) + -5 = -40 + 7n

Reorder the terms:
7(-4 + 2n) + -5 = -40 + 7n
(-4 * 7 + 2n * 7) + -5 = -40 + 7n
(-28 + 14n) + -5 = -40 + 7n

Reorder the terms:
-28 + -5 + 14n = -40 + 7n

Combine like terms: -28 + -5 = -33
-33 + 14n = -40 + 7n

Solving
-33 + 14n = -40 + 7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7n' to each side of the equation.
-33 + 14n + -7n = -40 + 7n + -7n

Combine like terms: 14n + -7n = 7n
-33 + 7n = -40 + 7n + -7n

Combine like terms: 7n + -7n = 0
-33 + 7n = -40 + 0
-33 + 7n = -40

Add '33' to each side of the equation.
-33 + 33 + 7n = -40 + 33

Combine like terms: -33 + 33 = 0
0 + 7n = -40 + 33
7n = -40 + 33

Combine like terms: -40 + 33 = -7
7n = -7

Divide each side by '7'.
n = -1

Simplifying
n = -1

See similar equations:

| 4ln(x-4)=4 | | (p+3)x^2+(2p+3)x+p+5=0 | | -.4x-9=.9 | | 5x+14=-28x-9x | | 19-3e=2-5(e+1) | | (y^2+2)(4y+7)= | | 2r^2+3r-20=0 | | (3y-3)(y+3)= | | 5x-3=2+6x | | 7=2r+5r | | -129=-3(8-7p) | | (y+9)(y+6)= | | 5x+1=14x-73 | | 6d-2(d-2)=3(d-12) | | (x+7)(2x^2-6x-2)= | | 5b-3=7b+11 | | 4x+10y=35 | | x(5-x)+4(x^1)= | | (5x-6)(4x-7)= | | (5x-7)(3x-2)= | | -7=12-k | | 4d-3=21 | | -32=x-17 | | 237x^2-56x= | | 8x^5y(9x^2+x^2y^3-8y^4)= | | 5a+13=7e-21 | | 3x^2-19x=63 | | 7y-5y=6 | | (4x-5)+(3x-1)= | | (4x^6)(-2x^5)(3x^9)= | | 24.2-18.5P=6.6P-1.9(9P+2) | | 12=k-2+6k |

Equations solver categories